2018
DOI: 10.1083/jcb.201703145
|View full text |Cite
|
Sign up to set email alerts
|

Dia1-dependent adhesions are required by epithelial tissues to initiate invasion

Abstract: How collective cell migration mediates tissue shape changes during the development of normal tissue or tumors is unclear. Fessenden et al. show that the formin Dia1 stabilizes adhesions of protruding MDCK cells during branching morphogenesis, permitting force generation against collagen and eventual tissue shape changes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…Our findings that the response to 1D guidance cues is not dependent on substrate rigidity nor cell contractility suggests that carcinoma cells can deploy a high-traction-independent approach for effective ECM pattern sensing and protrusion. To test our hypothesis and define the molecular mechanisms governing contact guidance in both high- and low-traction states, we first explored the role of Arp2/3-dependent actin nucleation and formins, which are required for effective transmission of traction force between FAs and the actin cytoskeleton 24 26 , 45 and have been recently reported to influence adhesion stability and 3D matrix deformation that influences invasion 26 , yet their role in contact guidance is less explored. Furthermore, both Arp2/3 and formins have been widely implicated in lamellipodia and filopodia dynamics 27 , 28 ; however, their role during distinct protrusion and motility events is not without controversy.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings that the response to 1D guidance cues is not dependent on substrate rigidity nor cell contractility suggests that carcinoma cells can deploy a high-traction-independent approach for effective ECM pattern sensing and protrusion. To test our hypothesis and define the molecular mechanisms governing contact guidance in both high- and low-traction states, we first explored the role of Arp2/3-dependent actin nucleation and formins, which are required for effective transmission of traction force between FAs and the actin cytoskeleton 24 26 , 45 and have been recently reported to influence adhesion stability and 3D matrix deformation that influences invasion 26 , yet their role in contact guidance is less explored. Furthermore, both Arp2/3 and formins have been widely implicated in lamellipodia and filopodia dynamics 27 , 28 ; however, their role during distinct protrusion and motility events is not without controversy.…”
Section: Resultsmentioning
confidence: 99%
“…As DSFs form the connection between adhesions and myofibrils, we hypothesized that reducing this connection could lead to less mature myofibrils. In nonmuscle cells, the actin filament nucleator DIAPH1 is known to be critical for focal adhesion growth and its depletion results in fewer and smaller focal adhesions ( Riveline et al , 2001 ; Fessenden et al , 2018 ). We previously showed that DIAPH1 is expressed in hiCMs using RNAseq ( Fenix et al , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, reduction of myosin activity promotes spreading [35] and increases invasion [58], potentially by decreasing adhesion lifetime [59]. Similarly, destabilizing adhesions through knockdown of the formin Dia1 reduces invasion [60], while stabilizing them through upregulation of paxillin enhances it [61]. Finally, cells are also able to remodel the ECM as they migrate, changing its material properties [62] and organization [63], which can in turn promote invasion [64].…”
Section: Migration Modes Depend On Ecm Geometry and Coupling Efficiencymentioning
confidence: 99%